Spontaneous Order Versus Central Planning: A comparison of MICHAEL POLANYI & F.A. VON HAYEK - Reimers, Patrick (REVISTA PROCESOS DE MERCADO, 2020)
This paper evaluates and compares the main philosophic and economic thoughts of the two great liberal minds Michael Polanyi and Friedrich A. von Hayek in regards to the concept of a ‘spontaneous order’. In several of their books and papers, both Michal Polanyi (1941, 1948, 1951) and F.A. von Hayek (1944, 1945, 1964, 1973) strongly emphasised on the impossibility of socialism and the superiority of a free market versus public interventionism. Both highlighted their conviction that central planning cannot be more efficient than a spontaneous order, since knowledge is dispersed (Hayek) and tacit (Polanyi). Although both shared very similar concerns in regards to economic matters, they did not always come to the same conclusions. Thus, also the differences between Polanyi’s and Hayek’s concepts will be discussed, such as Polanyi’s emphasis on defending subsystems as the basic units of society, and his focus on maximizing “public freedom”. Both came to different conclusions in regards to the institutional character of science, and even concluded somewhat differently on the character of knowledge. Most importantly, they developed different concepts on political economy and the ideal role of the State. Moreover, this paper will consider the impact of M. Polanyi on the concept of polycentricity and on the ideas of Elinor Ostrom, while also referring to the different understanding of the role of the State in the ideas of F.A. Hayek compared to other Austrian School economists, such as Murray N. Rothbard. In addition, the paper pretends to historically analyse the emergence of the term ‘spontaneous order’, showing that it is not the product of one mind’s design, but the consequence of the thoughts of several great minds, such as Carl Menger, Ludwig von Mises, F.A. von Hayek, Michael Polanyi, Walter Eucken, and Wilhelm Röpke. Keywords: liberalism, libertarianism, capitalism, Austrian school of economics, interventionism, collectivism, spontaneous order, dynamic efficiency, free market economy, polycentricity, catallactics, extended order, tacit knowledge, dispersed knowledge, F.A. Hayek, Michael Polanyi JEL Classification: A12, B10, B13, B25, H10, H40, K11, P10, P14, P16, P26, P48, P51 Resumen: Este artículo evalúa y compara los principales pensamientos económicos y filosóficos de las dos grandes mentes liberales Michael Polanyi y Friedrich A. von Hayek con respecto al concepto del orden espontáneo. En sus obras principales, tanto Michael Polanyi (1941, 1948, 1951) como F.A. von Hayek (1944, 1945, 1964, 1973) destacaron fuertemente la imposibilidad del socialismo y la superioridad de un mercado libre versus el intervencionismo público. Ambos estaban convencidos de que la planificación central no puede ser más eficiente que un orden espontáneo, ya que el conocimiento es disperso (Hayek) y tácito (Polanyi). Aunque ambos compartían preocupaciones muy similares con respecto a los asuntos económicos, no siempre llegaron a las mismas conclusiones. Por lo tanto, también se discutirán las diferencias entre los conceptos de Polanyi y Hayek, como el énfasis de Polanyi en defender los sub-sistemas como unidades básicas de la sociedad y su enfoque en maximizar la “libertad pública”. Ambos llegaron a conclusiones diferentes con respecto al carácter institucional de la ciencia y al carácter del conocimiento. Además, este artículo considerará sus diferentes conceptos sobre economía política y el papel ideal del Estado, y analiza el impacto de M. Polanyi en el concepto de policentrismo y en las ideas de Elinor Ostrom. Por otra parte, el artículo pretende analizar históricamente la aparición del término “orden espontáneo”, mostrando que no es producto del diseño de una sola mente, sino la consecuencia de los pensamientos de varias grandes mentes, como Carl Menger, Ludwig von Mises, FA von Hayek, Michael Polanyi, Walter Eucken y Wilhelm Röpke. Palabras clave: liberalismo, libertarismo, capitalismo, escuela austriaca de economía, intervencionismo, colectivismo, orden espontáneo, eficiencia dinámica, economía de libre mercado, policentrismo, orden extendido, conocimiento tácito, conocimiento disperso, F.A. Hayek, Michael Polanyi Clasificación JEL: A12, B10, B13, B25, H10, H40, K11, P10, P14, P16, P26, P48, P51